Palm oil plantation transportation management improving using economic information systems and Qm-Windows - Jumintono, Jumintono; Wiyatiningsih, Sri; Relawati, Rahayu; Yanita, Mirawati; Santi, Idum Satia (Institute of Society Transformation, 2022)
Limited information, mainly based on real economy as a tool for determining transportation infrastructure location, is one of the obstacles faced by oil palm plantation companies. This study aims to develop a management information system for transporting the Transportation of Fresh Fruit Bunches (FFB) in oil palm plantations with considering the economic analysis by combination of GIS and Qm-Windows. This research uses the descriptive method. The study was conducted at one of the oil palm plantations in Central Kalimantan. Data were analyzed using the post-classification change detection (PCCD) method and estimated costs using the transportation method with the Qm-Windows program's help. The results showed that the GIS with Arcgis 10.1 application could compile an inventory information system for oil palm plantation transportation. Cost estimation based on the Qm-Windows application can be used to determine the priority of transportation selection estimation with minimum cost. These applications can be applied as reference considerations for policymaking in managing oil palm FFB transportation management. © Institute of Society Transformation, 2022.